Post Varicella Necrotising Fasciitis Afflicting Upper Limb in Young Child: A Rare Case Report - Prabhu, Swarup; Hussain, Ayjaz; Gupta, Tarun (Lietuvos chirurgija, 2024)
Necrotising fasciitis is a common surgical emergency. Risk factors include immunosuppression, type 2 diabetes mellitus, chronic diseases like cirrhosis of liver and chronic kidney disease, malignancies, intravenous drug use, obesity, and age more than 60 years. Our case is of a 14 years old boy who presented with necrotising fasciitis (NF) of right upper limb post varicella of 10 days duration. Prompt diagnosis with aggressive surgical debridement was lifesaving in this case. Early reconstruction with split skin grafting escalated recovery resulting in a fully functional limb without any residual deficit. This case is a rare example of post varicella NF in a young child without any co-morbidities. Majority such cases are encountered by a general surgeon in an emergency setting. Hence, this report sensitises and enlightens the first responders about the existence of this rare entity.